Reviewing Bourdieu’s Critique of Opinion Polls and Notion of Reflexivity in the Public of Indonesia - Fardiah Oktariani Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2017)
In his writing,Bourdieu (1979)argued that public opinion that was measured in the simplified opinion polls or surveys, and were acknowledged only by the agent that made it, simply does not exist.But it doesnot necessarily mean he underestimatedthe construction of opinion polls, he also thought that opinion poll could still contributes to social science but it should be performed carefully. While Bourdieu might not explain the exact way to do this, he did come up with the suggestion of using reflexive attitude in social practice, especially in researches, to produce a more objective one. He introduced the notion of reflexivity as a way to overcome this question.This paper will then link the notion of reflexivity with the concept of cybernetics, and in particular the use ofblog as complement to evaluate public opinion resulted mainly from a simplified poll. An example of survey that was done in Indonesiais then used to analyze this argument toshows that it is plausible that Bourdieu’s argument still holds until present-day.While blog can come as a way for citizen to be an observer, its contribution to the sphere of democracy in Indonesia is arguably has not been properly attended.